Spirituality, religion and well-being facing colorectal cancer: a case study (Research, Society and Development, 2021)
Cancer is a dzsease that disrupts people's lives and their projects and perspectives for the future. Topics such as spirituality and religion have been increasingly studied in patients with serious illnesses. Thus, the aim of this study was to understand the perception of spirituality and religion of a patient diagnosed with colorectal cancer. This is a unique case study whose methodology was chosen for its ability to allow us to present a detailed description of a life experience. From a content analysis, three categories were found: diagnosis disclosure, coping strategies and feelings towards the cure. Being spiritual and religious is part of the interviewee's personal identity. She claims that she is charitable, kind and loving to all people and declares that her faith in Our Lady of Caravaggio is a story of devotion. She believes that this helped her to cope with the disease and influenced her well-being during and after treatment. After being cured of cancer, she thanks the blessings received and paid the promise she had made to the Saint for having cured her of the disease. She says that her faith helped her to overcome her illness, to give her more tranquility in life and not to be afraid to face difficult moments and death. The study allowed us to better understand the meanings of spirituality and religion as a supporting psycho-emotional apparatus in coping with the disease.